Al-Ijtihād al-Intiqā'ī and the Resolution of Issues in the Schools of Islamic Jurisprudence: A Study on the Implementation of the Concept of Al-Ijtihād al-Intiqā'ī in the Indonesian Religious Courts.: الاجتهاد الانتقائي وحل القضايا الفقهية المذهبية؛ دراسة عن تطبيق الاجتهاد الانتقائي في المحكمات الدينية الإندونيسية - Istiqlal, Ibnu Farhan; Meriza Isna Fadlilah; M. Ikhsanul Akhdza. E (Institut Muslim Cendekia, 2025)
The dynamic development of the times raises various new legal issues, including in the realm of Islamic family law. This research specifically aims to reveal how ijtihad intiqa'i can be applied in case settlement in Religious Courts in Indonesia, especially when it has to conflict with the classical law of a madhhab that is used as a role model, where there are differences of opinion among fiqh schools. This research uses a qualitative approach with a case study method. Primary data was obtained through a document study of Religious Court decisions and fiqh books as materials to analyze them. Data analysis was carried out using the theoretical framework of ijtihad intiqa'i. The results of the research intiqa'i ijtihad has a very important role in the dynamics of Islamic law in Indonesia. However, more systematic efforts need to be made to increase the capacity of judges in conducting ijtihad, as well as providing clearer regulations related to the application of ijtihad in religious courts.